Letter from John R. Brinkley to Minerva Telitha "Minnie" Jones, January 13, 1942, KHS BrinkleyJ-to-BrinkleyM-1942-January13 - Walker, Ky (2025)
John R. Brinkley II, a self-proclaimed doctor, was born July 8, 1885. While he is best known for his practice of xenotransplantation of goat testicles in an attempt to cure related to the prostate and impotence. Brinkley was the founder of his own radio station, KFKB, which broadcast everything from gospel readings, to music, to comedy. Brinkley also ran for governor of Kansas. While he was unsuccessful in these attempts, he nearly won twice, and to this day he is remembered as one of the earliest people to use radio broadcast for political campaigning. Throughout his life, John Brinkley accumulated many personal, professional, and political enemies. Within this letter, Brinkley mentions friends who have turned against him, including Dr. Horatio Dwight Osborn (a colleague of Brinkley’s; it is rumored Brinkley had bitten his ear off during a misunderstanding), Dr. L.L. Marshall (a once medical friend turned foe once he began to steal Brinkley’s patients), Dr. James R. Middlebrook (who also stole Brinkley’s patients for a cut-rate price), and Sam Rorex (a district attorney for Little Rock, Arkansas who refused to assist Brinkley with his ever growing bankruptcy). At the end of his life, Brinkley’s luck had run out. He was eventually stripped of his fraudulent medical license in multiple states, lost his radio stations, and began to have many lawsuits filed against him due to his medical malpractice, and along with his wife and six other associates, he was sued for mail fraud by the federal government. Brinkley would never see a trial for this mail fraud, however, as his health was rapidly declined. After suffering three heart attacks, two of which were critical, and a leg amputation, John R. Brinkley died on May 26, 1942 in San Antonio, Texas. Given the contents of the letter, “sugar” most likely refers to his wife, Minerva Telitha "Minnie" Jones. His wife, Minerva Telitha "Minnie" Jones, was born June 14, 1892 in Memphis Tennessee. On February 21st, 1916, she married John R. Brinkley at the age of 23. Their marriage lasted until Brinkley’s death in 1942. Minnie would go on to live until the age of 82, dying on January 8, 1980. This letter showcases how stressful the end of Brinkley’s life was and how many enemies he was beginning to accumulate. We also get a glimpse into how these troubles impacted his marriage and Minerva.